P04.71 LRIG2 promotes the proliferation of glioblastoma cells in vitro and in vivo through enhancing the PDGFRβ signaling pathways. (19th September 2018) - Xiao, Q; Dong, M; Cheng, F; Mao, F; Zong, W; Wu, K; Xie, R; Wang, B; Lei, T; Guo, D
Abstract: Background: The leucine-rich repeats and immunoglobulin-like domains (LRIG) gene family, comprising of LRIG1, 2 and 3, encodes integral membrane proteins. It is now well established that LRIG1 negatively regulates multiple growth factor signaling and is a proposed tumor suppressor, however the biological functions of LRIG2 remain largely unexplored. Previously, we demonstrated that LRIG2 promoted the growth of glioblastoma by positively regulating the EGFR signaling, the most common aberrant receptor tyrosine kinase (RTK) signaling in glioblastoma. Here, we further addressed the effects of LRIG2 on the proliferation of glioblastoma and the possible mechanisms underlying the regulation of LRIG2 on PDGFRβ signaling, another common oncogenic RTK signal in glioblastoma. Material and Methods: A total of 40 glioblastoma samples were surgically obtained and subjected to immunohistochemical staining for LRIG2 and PDGFRβ. U87 glioblastoma cells were stably transduced with retroviral vectors to upregulate or downregulate the expression of LRIG2. CCK-8 assay and soft agar colony formation assay were used to detect the PDGF-BB-induced proliferation of glioblastoma cells, respectively. Flow cytometric analysis was used to investigate the cell cycle progression. Subcutaneous tumor formation in nude mice was performed to investigate the tumor growth in vivo . Immunofluorescence and Co-IP were used to detect the protein interaction, and western blot was used to examine the signaling pathway proteins. Results: First, we found that the expression levels of endogenous LRIG2 and PDGFRβ varied notably in human glioblastoma and the LRIG2 expression level was positively correlated with the expression level of PDGFRβ. Further, to the best of our knowledge, we demonstrated for the first time that LRIG2 promoted the PDGF-BB-induced proliferation of glioblastoma cells in vitro and in vivo through regulating the PDGFRβ signaling mediated cell cycle progression. Mechanistically, LRIG2 has the ability to physically interact with PDGFRβ, promoting the total expression level and the activation of PDGFRβ, and enhancing its downstream pathways of Akt and signal transducer and activator of transcription 3 (stat3) and the effectors of key regulators of cell cycle progression, resulting in the promotion of glioblastoma proliferation. Conclusion: These data indicated that LRIG2 may serve as a tumor promoter gene in gliomagenesis by positively regulating PDGFRβ signaling, another important oncogenic RTK signal besides our previously reported EGFR signaling in glioblastoma modulated by LRIG2, and validated LRIG2 as a promising potential therapeutic target for the treatment of glioblastoma characterized by multiple aberrant RTK signaling. Supported by grants from the National Natural Science Foundation of China (grant nos. 81702480 and 81472364).